Yuri Gagarin and the race to space - Hubbard, Ben 1973- (Chicago, Illinois Heinemann Raintree, 2016)
"Join Yuri Gagarin on his journey into space! This book examines the extraordinary life of the first astronaut in space, from his early life to his first trip aboard a Russian spacecraft. Discover what the space race was and other developments happening at the time. Find out about the rigorous training that astronauts undergo and how they prepare for a journey into the unknown."--
Space pioneer -- Child of war -- Cosmonaut Gagarin -- Spacecraft -- Countdown begins -- April 1961 -- Most famous man in the world -- Gagarin's message
The world around us (Outer space)
Includes bibliographical references (page 46) and index
1 2 13
NEW_ZTN_GN
Keywords: Gagarin, Yuri Alekseyevich -- 1934-1968 -- Juvenile literature; Vostok (Spacecraft) -- Juvenile literature; Astronauts -- Soviet Union -- Biography -- Juvenile literature; Manned space flight -- History -- Juvenile literature